Quasi‐distributed Interference Coordination for HSPA HetNet - Zhang, Chi; Chang, Yongyu; Qin, Shuqi; Yang, Dacheng (ETRI journal, 2014)
The heterogeneous network (HetNet) has been discussed in detail in the Long‐Term Evolution (LTE) and LTE Advanced standards. However, the standardization of High‐Speed Packet Access HetNet (HSPA HetNet) launched by 3GPP is pushing at full steam. Interference coordination (IC), which is responsible for dealing with the interference in the system, remains a subject worthy of investigation in regard to HSPA HetNet. In this paper, considering the network framework of HSPA HetNet, we propose a quasi‐distributed IC (QDIC) scheme to lower the interference level in the co‐channel HSPA HetNet. Our QDIC scheme is constructed as slightly different energy‐efficient non‐cooperative games in the downlink (DL) and uplink (UL) scenarios, respectively. The existence and uniqueness of the equilibrium for these games are first revealed. Then, we derive the closed‐form best responses of these games. A feasible implementation is finally developed to achieve our QDIC scheme in the practical DL and UL. Simulation results show the notable benefits of our scheme, which can indeed control the interference level and enhance the system performance.